2014
DOI: 10.4103/2225-4110.128906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Goshajinkigan, Hachimijiogan, and Rokumigan on Mechanical Allodynia Induced by Paclitaxel in Mice

Abstract: Peripheral neuropathy is a major dose-limiting side effect of the chemotherapeutic agent paclitaxel. This study examined whether the three related traditional herbal formulations, goshajinkigan (GJG; 牛車腎氣丸 Niú Chē Shèn Qì Wán), hachimijiogan (HJG; 八味地黃丸 Bā Wèi Dì Huáng Wán), and rokumigan (RMG; 六味丸 Liù Wèi Wán), would relieve paclitaxel-induced mechanical allodynia in mice. A single intraperitoneal injection of paclitaxel (5 mg/kg) induced mechanical allodynia, which peaked on day 14 after injection. On day 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…daily) in mice, although Jesengshingi-Hwan could not suppress cancer-induced allodynia [43]. Andoh et al [111] also reported that Jesengsingi-Hwan (0.1-1.0 g/kg, p.o.) markedly inhibited paclitaxel-induced mechanical allodynia in mice.…”
Section: Jesengshingi-hwanmentioning
confidence: 99%
“…daily) in mice, although Jesengshingi-Hwan could not suppress cancer-induced allodynia [43]. Andoh et al [111] also reported that Jesengsingi-Hwan (0.1-1.0 g/kg, p.o.) markedly inhibited paclitaxel-induced mechanical allodynia in mice.…”
Section: Jesengshingi-hwanmentioning
confidence: 99%
“…However, serious drawbacks hamper the clinical application of PTX. First, PTX lacks selective cytotoxicity against cancer cells and frequently leads to serious side effects . Poor water solubility of PTX (0.3 μg/mL) is another concern that significantly reduces its wider clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…First, PTX lacks selective cytotoxicity against cancer cells and frequently leads to serious side effects. 2 Poor water solubility of PTX (0.3 :g/mL) is another concern that significantly reduces its wider clinical application. To enhance its water solubility, PTX is currently formulated as a 50:50 mixture of Cremophor EL and ethanol (Taxol).…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary experiments, a single administration of aucubin did not alleviate paclitaxelinduced allodynia at day 14 after the paclitaxel injection (data not shown), which was similar to the effect observed with goshajinkigan. 9) This suggests that aucubin requires repetitive administration to produce an anti-allodynic effect. In addition, the results of the present study show that repetitive administration of aucubin, but not its metabolite catalpol, inhibits the exacerbation of paclitaxel-induced mechanical allodynia, which complements the results in our previous report.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Our previous study has been shown that repetitive administration of goshajinkigan extract as a prophylactic inhibits the exacerbation of paclitaxel-induced mechanical allodynia in mice. 9) We also showed that aucubin, which is an iridoid glycoside and the main component of Plantaginis Semen, plays an important role in the anti-allodynic action of goshajinkigan. 10) However, the mechanisms underlying the anti-allodynic activity of aucubin are not understood completely.…”
mentioning
confidence: 99%